Correlation Between Learning Orientation Culture and Teachers’ Entrepreneurial Innovative Behavior - Rahmawati, Kuncoro Dewi; Kurniawan, Jimmy Ellya (Universitas Ciputra Surabaya, 2021)
Conditions during the COVID-19 pandemic are continuously requiring teachers to improve their use of innovative behavior at work. Several previous studies have proven that learning orientation culture has an influence on innovative behavior. However, all of these studies have been conducted in the industrial sector. The current study aims to examine the relationship between learning orientation culture and teacher’s innovative behavior. Respondents of the study included 36 teachers from six cities in Java, Indonesia: Surabaya, Malang, Semarang, Salatiga, Surakarta and Yogyakarta. The results show that there was no relationship between learning orientation culture and teacher’s innovative behavior. Meanwhile, in the current study, only the intra-organizational knowledge sharing component had a significant correlation with teacher’s innovative behavior. Different job characteristics for teachers and employees in the industrial sector are the main point of argument in the discussion of this research.